Novel peptide conjugate vaccines - GRIFFOEN ARJAN WILLEM; VAN LOON KARIN; HUIBERS, ELISABETH JOHANNA MARIA (2025)
The present invention provides novel fusion polypeptides and compositions comprising the same. The fusion polypeptides are capable of triggering and/or enhancing an immune response against the peptide sequence of interest contained therein and are thus useful in vaccinating or treating a mammalian subject. Kits comprising the fusion polypeptides are also provided. 本发明提供了新的融合多肽及包含其的组合物。融合多肽能够触发和/或增强针对其中包含的感兴趣的肽序列的免疫反应，并因此可用于疫苗接种或治疗哺乳动物受试者。还提供了包含融合多肽的试剂盒。